The Macrophages-Microbiota Interplay in Colorectal Cancer (CRC)-Related Inflammation: Prognostic and Therapeutic Significance - Mola, Silvia (Int J Mol Sci, 2020)
Tumor-associated macrophages (TAMs) are the main population of myeloid cells infiltrating solid tumors and the pivotal orchestrators of cancer-promoting inflammation. However, due to their exceptional plasticity, macrophages can be also key effector cells and powerful activators of adaptive anti-tumor immunity. This functional heterogeneity is emerging in human tumors, colorectal cancer (CRC) in particular, where the dynamic co-existence of different macrophage subtypes influences tumor development, outcome, and response to therapies. Intestinal macrophages are in close interaction with enteric microbiota, which contributes to carcinogenesis and affects treatment outcomes. This interplay may be particularly relevant in CRC, one of the most prevalent and lethal cancer types in the world. Therefore, both macrophages and intestinal microbiota are considered promising prognostic indicators and valuable targets for new therapeutic approaches. Here, we discuss the current understanding of the molecular circuits underlying the interplay between macrophages and microbiota in CRC development, progression, and response to both conventional therapies and immunotherapies.